Evaluating the Effect of Fenofibrate Towards the Progression of Diabetic Retinopathy: A Systematic Review - Livinia Gabriela Pontoh; Karel Pandelaki; Yuanita Asri Langi; Bisuk Parningotan Sedli; Gloria Notaria Pandelaki (PP PERKENI, 2025)
The rising prevalence of diabetic retinopathy (DR) among diabetic patients necessitates innovative therapeutic strategies. Fenofibrate, primarily known for its lipid-loweringeffects, has gained attention for its potential role in mitigating DR progression. This study aims to evaluate the efficacy of fenofibrate in reducing the progression of diabetic retinopathy. A comprehensive search was done on three electronic databases, including PubMed, Scopus, and ProQuest up to 3 January 2025. We included all studies that are clinical trials orobservational by design published within the last 15 years. The outcome of interest in this study is the progression or worsening of DR. All eligible studies were assessed using the Cochrane riskof bias tool 2.0 for randomized clinical trials, and the risk of bias in non-randomized studies - of interventions.Result: A total of 5 studies encompassing 2 RCT and 3 retrospective cohort studies with a totalof 250.835 patients, consisting of 101.026 (40.3%) males, with an overall mean age of 64.3 ± 9.5 years old. Based on the risk of bias assessment, all five studies fall in the low to moderate risk ofbias. Four studies show that fenofibrate significantly reduces the risk of DR progression, while one study shows no significant reduction. Two studies also indicate the efficacy of fenofibrate inreducing the development of macular edema. This study solidifies the efficacy of fenofibrate in reducing the risk of DR progression and the development of macular edema.